Assessment of physicians' and medical majors' knowledge of asthma basics: Current results of the ASSA-II study - Roman A. Bontsevich; Alina V. Mikhno; Oksana V. Dudchenko; Galina A. Batisheva; Galina G. Prozorova; Tatiana M. Shagieva; Elena V. Miliutina; Yuliya M. Dronova; Olena V. Myronenko; Galina G. Ketova; Valeriya O. Barysheva; Elena V. Luchinina; et al. (Belgorod National Research University, 2019)
Introduction: Bronchial asthma is a disease characterized by chronic inflammation of the airways. At present, about 235-300 million people suffer from asthma, and this number continues to grow. This pathology is also common in children. It causes significant social and economic damage worldwide. Severe forms of asthma are difficult to treat. Thus, a continuous improvement of doctors' knowledge in this field is of great importance. Methods: The analysis of an anonymous survey of physicians and senior medical students was used in the research. Results: The study revealed both an average level of basic knowledge in asthma etiology and pathogenesis among the physicians and senior medical students and the significant differences in their knowledge regarding clinical picture and treatment of asthma. Only 49.2% of students and 56.0% of doctors were able to choose the correct definition of asthma from the suggested answers; 65.7% of students and 69.9% of doctors correctly indicated the main clinical and laboratory markers of asthma; 60.2% of students and 91.0% of doctors determined the correct combination of drugs in one delivery device; and 75.9% of students and 91.2% of doctors selected the correct basic asthma therapy depending on the severity. Conclusion: Basing on the results obtained it was recommended to introduce additional educational activities on the diagnosis and therapy of asthma among medical majors and physicians.